Employment status transitions in employees with and without chronic disease in the Netherlands - de Boer, Angela G. E. M. (Int J Public Health, 2018)
OBJECTIVES: Objectives were to: (1) longitudinally assess transitions in employment status of employees with and without chronic disease; and (2) assess predictors of exit from paid employment. METHODS: Transitions in employment status at 1- and 2-year follow-up were assessed in a longitudinal cohort study of employees aged 15–63 years. Generalised estimating equations (GEE) and logistic regression analyses were performed to analyse differences in transitions and identify sociodemographic, health- and work-related predictors. RESULTS: At 1- and 2-year follow-up, 10,038 employees (37% with chronic disease) and 7636 employees responded. Employees with chronic disease had higher probability of leaving paid employment [OR 1.4 (1.1–1.6)] and unemployment, disability pension and early retirement. Employees without chronic disease had higher chance of moving into self-employment or study. At 2-year follow-up, employees with cardiovascular disease (15%), chronic mental disease (11%), diabetes (10%) and musculoskeletal disease (10%), had left paid employment most often. Higher age, poor health, burnout, low co-worker support and chronic disease limitations were predictors for leaving paid employment. CONCLUSIONS: Employees with chronic disease leave paid work more often for unfavourable work outcomes.